Clean-in-place monitoring of different food fouling materials using ultrasonic measurements. (October 2019) - Escrig, Escrig, J.; Woolley, E.; Rangappa, S.; Simeone, A.; Watson, N.J.
Abstract: Clean-in-Place is an autonomous technique used to clean the internal surfaces of processing equipment in the food and drink sector. However, these systems clean for a longer time than required with negative economic and environmental impacts. In this work, an ultrasonic sensor system was developed to monitor the cleaning of different food fouling materials at laboratory scale. The fouling removal of three different food materials was also studied at different cleaning fluid temperatures. The three food materials had different cleaning mechanisms, which could be monitored successfully with the ultrasonic system. Tomato paste and gravy appeared to be cleaned by mechanical forces whereas malt extract dissolved into the cleaning water. The results yielded from the cleaning of the malt was found to be repeatable whereas the tomato and gravy were more variable between repeat experiments. It was found that changes in recorded ultrasonic signals were mainly affected by the area of fouling that covered the transducer's active element. Highlights: Ultrasonic method used to monitor the cleaning of different fouling material relevant to food sector. Ultrasonic technique delivers repeatable results for a range of materials and two different temperatures. Tomato paste and gravy clean by mechanical removal whereas malt cleans predominantly by dissolution. Ultrasonic technique more sensitive to the area of fouling covering the transducer footprint than the fouling thickness.